Fuzzy Logic Algorithm and Analytic Network Process (ANP) for Boarding House Search Recommendations - Gunawan, Wawan (ILKOM Jurnal Ilmiah, 2021)
The process of finding a boarding house is usually done manually or by visiting the boarding house one by one. Several choices of boarding houses make boarding house seekers have to make choices according to the desired criteria, so it takes quite a long time. A decision support system is a system that can be used to help make decisions based on existing criteria in determining several alternatives to be selected. The method used in this research is the Analytic Network Process (ANP) and Fuzzy Logic method. This study uses several criteria in providing recommendations including distance, price, facilities, security, number of spaces, parking space and comfort. The weighting of these criteria uses the fuzzy logic method based on the priority scale determined by the boarding house finder. This system will provide a recommendation order for boarding houses based on the results of the calculation process using the ANP method and weighting using fuzzy logic. a value of 6.52%.